1977
DOI: 10.1002/jez.1402000102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 5‐bromodeoxyuridine on the postnatal development of the rat testis

Abstract: The effects of 5-bromodeoxyuridine (BrdU) on postnatal testicular development were studied in rats treated on the second, third and fourth days of life. Testes were removed for study at 5, 15 and 35 days of age. Body weights and diameters of seminiferous cords and tubules were significantly less in the treated than control animals. At 15 days of age fewer pachytene spermatocytes were present in treated animals. At 35 days of age the testes of treated animals contained fewer canalized cords. Spermatids exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The huge impact of this method on the scientific progress in the field and some initial data demonstrating the BrdU application during pregnancy in rodents did not have any obvious toxic effects on the progeny in terms of litter size, pup weight and neurological function (Miller and Nowakowski 1988), led to the neglection of any possible side effects of BrdU incorporation. This is surprising, since earlier studies had demonstrated quite unambiguously that BrdU has detrimental effects on fetal and (n=5) neonatal development (Garner 1974;Agnish and Kochhar 1976;Pollard et al 1976;Barasch and Bressler 1977). Moreover, more recent work has demonstrated that BrdU impairs proliferation of mouse and human fibroblasts, of lymphocytes, and of carcinoma cell lines in vitro (Poot et al 1994;Diermeier et al 2004).…”
Section: Discussionmentioning
confidence: 75%
“…The huge impact of this method on the scientific progress in the field and some initial data demonstrating the BrdU application during pregnancy in rodents did not have any obvious toxic effects on the progeny in terms of litter size, pup weight and neurological function (Miller and Nowakowski 1988), led to the neglection of any possible side effects of BrdU incorporation. This is surprising, since earlier studies had demonstrated quite unambiguously that BrdU has detrimental effects on fetal and (n=5) neonatal development (Garner 1974;Agnish and Kochhar 1976;Pollard et al 1976;Barasch and Bressler 1977). Moreover, more recent work has demonstrated that BrdU impairs proliferation of mouse and human fibroblasts, of lymphocytes, and of carcinoma cell lines in vitro (Poot et al 1994;Diermeier et al 2004).…”
Section: Discussionmentioning
confidence: 75%
“…This method has the advantage over the more traditional 3 [H]thymidine labelling in that it can be detected immunohistochemically, which can be combined more easily with various phenotypic markers such as those used for neuronal or glial cells. However, there are many reports of its toxicity during embryonic (Garner, 1974; Agnish & Kochhar, 1976; Pollard et al ., 1976; Dribin & Jacobson, 1978; Bannigan & Cottell, 1991; Nagao et al ., 1997; Kolb et al ., 1999; Tencer & Brachet, 2000) and neonatal development (Barasch & Bressler, 1977). This toxicity has led to malformations in the offspring when BrdU has been injected into the mother during gestation, with time of administration during development and doses used being critically important in determining the abnormalities reported.…”
Section: Introductionmentioning
confidence: 99%
“…BrdU competes with thymidine for sites on the replicating DNA strand, and in culture there can be almost total substitution of BrdU for thymidine in the nuclear DNA (Bick and Davidson, 1974). At various concentrations, BrdU has been found to produce various cellular abnormalities both in vitro (Stockdale et al, 1964;Wilt and Anderson, 1972;Trencer and Brachet, 1973;Agnish and Kochhar, 1976a,b;Pollard et al, 1976;Barasch and Bressler, 1977;Dribin and Jacobson, 1978) and in vivo (DiPaolo, 1964;Meller et al, 1973;Webster et al, 1973;Younkin and Silberberg, 1973;Yu, 1976;Bannigan and Langman, 1979;Shah et al, 1991;Nagao et al, 1997).…”
mentioning
confidence: 99%